Access to gambling services among vulnerable population: Implications of online sports betting for sustainable development in Nigeria - Gbadegesin, Adeniyi S.; Akintunde, Elijah A. (Modern Geográfia, 2025)
Information and communication technology has increased access to gambling services and made it highly prevalent among youths. The youthful population in Nigeria is constantly confronted with several negative psychological implications of betting. Using a survey method for primary data collection, this study examined access, determinants, and patronage of online sports betting among 300 respondents. The results show that most respondents were young adults within the 18–28 age category. The majority were male and had attained tertiary-level education. About 79% of the respondents were students with an income level below N30,000.00. Additionally, 51.7% of the respondents had engaged in some form of online betting to earn money or gain other benefits, while 48.3% had not. This study indicates that online betting is quite popular, and physical access to betting locations is relatively easy for most respondents.